2012
DOI: 10.1177/0886260512441072
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Unintended Pregnancy Among Bangladeshi Women

Abstract: This study examined the relationship between intimate partner violence (IPV) and unintended pregnancy using data from women reporting IPV in the 2007 Bangladesh Demographic Health Survey. The analysis included 4,695 married women, aged 15 to 40 years, who had at least one birth in the last 5 years. Bivariate and multiple logistic regression analyses were performed to assess the relationship between IPV and pregnancy. About one third (30.4%) of women were abused physically and/or sexually and about one third (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 37 publications
6
49
1
Order By: Relevance
“…Results from this study are consistent with other studies that have reported an association between partner violence and unintended pregnancy (Han and Stewart 2014;Pallitto et al 2013;Rahman et al 2012;Stephenson et al 2008). A recent study that analyzed multi-country data from the World Health Organization reported that women with a history of IPV had significantly higher odds of unintended pregnancy and induced abortion, even after controlling for socioeconomic and demographic factors (Pallitto et al 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results from this study are consistent with other studies that have reported an association between partner violence and unintended pregnancy (Han and Stewart 2014;Pallitto et al 2013;Rahman et al 2012;Stephenson et al 2008). A recent study that analyzed multi-country data from the World Health Organization reported that women with a history of IPV had significantly higher odds of unintended pregnancy and induced abortion, even after controlling for socioeconomic and demographic factors (Pallitto et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…However, the conceptual model did not directly include the role of partners or partner support in decision-making, especially among racial and ethnic minority women. While previous studies have assessed the relationship between IPV and unintended pregnancy, few have focused on Hispanic/Latina and Asian women (Cripe et al 2008;Rahman et al 2012;Raj and McDougal 2015;Stephenson et al 2008;Stockman, Hayashi, and Campbell 2015) with inconsistent results (Martin and Garcia 2011;Martin-de-Las-Heras et al 2015). Further, to the authors' knowledge, no previously published studies have used structural equation modeling (SEM) to assess IPV, unintended pregnancy, and partner factors using a nationally representative dataset.…”
Section: Introductionmentioning
confidence: 93%
“…Conversely, socioeconomic status was not found to be associated with unplanned pregnancy in a UK study, where contraception is available for free [56]. Intimate partner violence may be causally associated with unplanned pregnancy due to an increased risk of sexual coercion, and sabotage of contraception [152,153]. Substance use before pregnancy may be causally associated with unplanned pregnancy, as it increases the likelihood of not using contraception [148,154].…”
Section: Unplanned Pregnancymentioning
confidence: 90%
“…Other factors associated with an increased risk of unplanned pregnancy include low SES, single marital status, exposure to intimate partner violence, smoking, illicit drug use and younger maternal age, while religion is associated with a decreased risk [53,54,56,134,135,152]. Some of these factors may be causal and others may be risk markers for unplanned pregnancy due to their association with other causal factors.…”
Section: Unplanned Pregnancymentioning
confidence: 99%
“…Haddadet al [33] conducted a study in Jordan and found that 39% of the participating women reported emotional abuse, while 30% reported physical abuse and 6% reported sexual abuse. Three studies conducted in Bangladesh identified that Muslim women were more likely to experience all forms of IPV than their non-Muslim counterparts [34][35][36]. However, a fourth study by Dalalet al [37] found the same differences between Muslim and non-Muslim women in all forms of abuse except for physical abuse.…”
Section: Prevalence and Types Of Abusementioning
confidence: 99%